Gluconeogenesis in the kidney cortex. Flow of malate between compartments - Rognstad, R. (1970)
1. Kidney-cortex slices from starved rats were incubated with l-[U-(14)C]lactate or l-[U-(14)C]malate plus unlabelled acetate and the specific radioactivity of the glucose formed was determined. In parallel experiments the specific radioactivity of the glucose formed from [1-(14)C]acetate plus unlabelled l-lactate and l-malate was determined. 2. By analytical methods the major products formed from the substrates were measured. The glucose formed was purified by paper chromatography for determination of specific radioactivity. 3. The specific radioactivity of the glucose formed from l-[U-(14)C]lactate agrees with predictions of a model based on interaction of the gluconeogenic and the oxidative pathways. 4. The specific radioactivity of the glucose formed from l-[U-(14)C]malate agrees with the predicted value if rapid malate exchange between the cytosol and mitochondria is assumed. 5. The rate of malate exchange between compartments was estimated to be rapid and at least several times the rate of glucose formation. 6. The specific radioactivity of the glucose formed from [1-(14)C]acetate plus unlabelled l-lactate or l-malate agrees with the predictions from the model, again assuming rapid malate exchange between compartments. 7. Malate exchange between compartments together with reversible malate dehydrogenase activity in the mitochondria and cytosol also tends to equilibrate isotopically the NADH pool in these compartments. (3)H from compounds such as l-[2-(3)H]lactate, which form NAD(3)H in the cytosol, appears in part in water; and (3)H from dl-β-hydroxy[3-(3)H]butyrate, which forms NAD(3)H in the mitochondria, appears in part in glucose, largely on C-4.